Enhancing cancer therapy: advanced nanovehicle delivery systems for oridonin - Su, Yilin; Liu, Lisha; Lin, Chongyang; Deng, Dashi; Li, Yunfei; Huang, Mou; Wang, Yu; Ling, Kangqiu; Wang, Haobing; Chen, Qiyu; Huang, Guixiao (Frontiers in Pharmacology, 2024)
Oridonin (ORI), an ent-kaurane diterpenoid derived from Rabdosia rubescens (Hemsl.) H.Hara, serves as the primary bioactive component of this plant. It demonstrates a broad spectrum of therapeutic activities, including moderate to potent anticancer properties, alongside anti-inflammatory, antibacterial, antifibrotic, immunomodulatory, and neuromodulatory effects, thus influencing diverse biological processes. However, its clinical potential is significantly constrained by poor aqueous solubility and limited bioavailability.In alignment with the approach of developing drug candidates from natural compounds, various strategies, such as structural modification and nanocarrier systems, have been employed to address these challenges. This review provides an overview of ORI-based nanodelivery systems, emphasizing their potential to improve the clinical applicability of oridonin in oncology. Although some progress has been made in advancing ORI nano-delivery research, it remains insufficient for clinical implementation, necessitating further investigation.